A comparative study on temperature variance and compact heat exchanger performance by using different fluid blends - S. Hasu, Basawaraju; G. V. Satyan Rao, Dr (International Journal of Engineering and Technology, 2018)
Compact heat exchangers are the critical cryogenic components which are characterized on its heat transfer which is enhanced as per the transfer rate per unit volume surface area of the exchanger. The design can be varied and authorized based on the flow (counter) which is fabricated for industrial and future applications. The performance of the exchanger is found by obtaining difference in mass flow rates. In this research we have taken blends of three different fluids which are mixed up with water to find the temperature variance and performance during different time with varying different flow rates and temperatures. Here in such cases the pressure is kept constant for both hot and cold sides. Due to variance in different temperatures and flows the mass flow rates according the time variance which gradually increases. Various working fluids considerations have been done for minimizing the pressure losses that are presented or obtained. The fluid blends like IPEX coolant, Castrol, Shell Diala S4ZX-1 has taken as blends with 2% and 4% blend mixtures with distilled water. The temperatures are varied two times during the flow that is 600c and 800c and each fluid is enhanced at both these temperatures. Finally we can obtain the better flow rate for the mixtures taken for all the fluids. Temperature variance is shown for all the blends with respect to the time intervals taken that is for 600sec and the values is authorized for each 60sec. with this we have present the best blend percentage mixture among the fluid blends taken with respect mixed proportions.Â Â